2020
DOI: 10.1038/s41467-020-17980-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the cervical environment is associated with increased antibiotic susceptibility in Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae is an urgent public health threat due to rapidly increasing incidence and antibiotic resistance. In contrast with the trend of increasing resistance, clinical isolates that have reverted to susceptibility regularly appear, prompting questions about which pressures compete with antibiotics to shape gonococcal evolution. Here, we used genome-wide association to identify loss-of-function (LOF) mutations in the efflux pump mtrCDE operon as a mechanism of increased antibiotic susceptibility an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 91 publications
0
64
0
1
Order By: Relevance
“…These newly sequenced genomes were combined with those of 1066 publicly available genomes from 14 studies spanning 35 countries: USA, Japan, Canada, UK, Spain, Brazil, Portugal, New Zealand, Hungary, Norway, Ireland, Greece, Sweden, Slovenia, Germany, Poland, Belarus, Denmark, Slovakia, Belgium, Australia, Austria, Italy, Netherlands, France, Cyprus, Latvia, Malta, Russia, Philippines, Bulgaria, Chile, India, Finland, and Estonia (ordered by frequency) [ 9 , 11 , 13 23 ] (see Additional file 2 : Table S1 for details). The publicly available genomes were selected based on a tree constructed in our previous study [ 24 ] such that they formed a group at the core-genome level.…”
Section: Methodsmentioning
confidence: 99%
“…These newly sequenced genomes were combined with those of 1066 publicly available genomes from 14 studies spanning 35 countries: USA, Japan, Canada, UK, Spain, Brazil, Portugal, New Zealand, Hungary, Norway, Ireland, Greece, Sweden, Slovenia, Germany, Poland, Belarus, Denmark, Slovakia, Belgium, Australia, Austria, Italy, Netherlands, France, Cyprus, Latvia, Malta, Russia, Philippines, Bulgaria, Chile, India, Finland, and Estonia (ordered by frequency) [ 9 , 11 , 13 23 ] (see Additional file 2 : Table S1 for details). The publicly available genomes were selected based on a tree constructed in our previous study [ 24 ] such that they formed a group at the core-genome level.…”
Section: Methodsmentioning
confidence: 99%
“…In Australia, significant differences in levels of resistance and decreased susceptibility were identified from gonococcal isolates derived from males versus females for all antimicrobials assessed [ 36 ]. Furthermore, it was recently suggested that genomic adaptation of gonococcal strains to the cervical environment is associated with increased antimicrobial susceptibility [ 37 ]. Regarding anatomical site of infection, pharyngeal gonorrhoea has been more common among MSM and gonococcal resistance to β-lactam antimicrobials, including the ESCs, may emerge in the pharynx through the acquisition of genetic AMR determinants from non-gonococcal commensal Neisseria species.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, lineage 2c also included a rare isolate lacking an fhbp gene and therefore unable to express fHbp which has also previously been implicated in adaptation to the anogenital niche [ 18 ]. None of the anogenital isolates possessed LOF mutations in mtrC that have been associated with cervical infection in gonococci and urogenitally adapted meningococci from uretheritis outbreaks among heterosexual males [ 19 ]. One possible explanation for this is that cc4821 isolates were all isolated from MSM and the cervix may not have been encountered in recent ancestral isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in gonococci found an association between loss of function (LOF) mutation in the efflux pump component, MtrC, and cervical infection. This extended to US_NmUC in which 8.7% of isolates possessed LOF mutations versus 0.62% in a large invasive disease collection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%